Development of Wheat-Aegilops caudata Introgression Lines and Their Characterization Using Genome-Specific KASP Markers - Grewal, Surbhi; Othmeni, Manel; Walker, Jack; Hubbart-Edwards, Stella; Yang, Cai-yun; Scholefield, Duncan; Ashling, Stephen; Isaac, Peter; King, Ian P.; King, Julie (Frontiers in Plant Science, 2020)
Aegilops caudata L. [syn. Ae. markgrafii (Greuter) Hammer], a diploid wild relative of wheat (2n = 2x = 14, CC), is an important source for new genetic variation for wheat improvement due to a variety of disease resistance factors along with tolerance for various abiotic stresses. Its practical utilisation in wheat improvement can be facilitated through the generation of genome-wide introgressions leading to a variety of different wheat–Ae. caudata recombinant lines. In this study, we report the generation of nine such wheat–Ae. caudata recombinant lines which were characterized using wheat genome-specific KASP (Kompetitive Allele Specific PCR) markers and multi-colour genomic in situ hybridization (mcGISH). Of these, six lines have stable homozygous introgressions from Ae. caudata and will be used for future trait analysis. Through a combination of molecular and cytological analysis of all the recombinant lines, we were able to physically map 182 KASP markers onto the seven Ae. caudata chromosomes, of which 155 were polymorphic specifically with only one wheat subgenome. Comparative analysis of the physical positions of these markers in the Ae. caudata and wheat genomes confirmed that the former had chromosomal rearrangements with respect to wheat, as previously reported. These wheat–Ae. caudata recombinant lines and KASP markers provide a useful genetic resource for wheat improvement with the latter having a wider impact as a tool for detection of introgressions from other Aegilops species into wheat.